Pengembangan Bahan Ajar Untuk Menumbuhkan Karakter Penguasaan Diri Pada Anak Sekolah Minggu Di Jemaat Imanuel Oenesu - Andra Angelia Lodo; Johana Manubey; Elidat Benyamin Suan (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2022)
Develompment of Teaching Materials to Grow Self-Control for Sunday School Children at GMIT Imanuel Oenesu.Christian Religious Education is an education centered on Christianity based on the teachings of Jesus Christ in the Bible. One form of Christian education carried out by the church is Sunday school. Sunday School is a place for children to be able to learn about the truth of God's word through the teachings contained in the teaching materials held by each Church. Of course, the teaching contains about how children will have the right mindset and pattern of behavior in accordance with the truth of the word, but it does not specifically teach children of a certain age about the characters contained in the fruit of the spirit, especially self-control. So, this study aims to produce products in the form of printed teaching materials that can teach the character of self-control for Sunday School children, especially 9-12 year old group. The development of self-mastery teaching materials is carried out using the Dick & Carey model, with data analysis methods compiled qualitatively and quantitatively which discussed descriptively. This research was conducted on the GMIT congregation Imanuel Oenesu, by obtaining the percentage results on the content expert test 96%, media expert 100% and design expert 92% as well as the small group test on three teachers namely 99.6% and five people in charge 99.1 % so that it can be stated that this self-control teaching material can grow the character of self-control in the children of responsibility as well as the teacher. Key words: Development; Self-Control; Sunday School; Teaching Materials.